RE-DRAWING INTERIOR SPACE: HABITATION PRACTICE AS ARCHITECTURAL METHOD - Barkouta, Yanna (Design/Arts/Culture, 2024)
The subject of this article entails an endeavor to spatially interpret a synchronicity labeled as a "crisis," or more fittingly, as a "permacrisis." Initially, the concept of crisis will be explored in conjunction with the hermeneutics of "normalcy." Subsequently, the article will scrutinize the spatial manifestations of the crisis, placing a particular emphasis on habitation and housing dynamics. To this end, our focus will shift to Greece, specifically the city of Athens, where the crisis intertwines with habitation practices. Consequently, the article will juxtapose a theoretical exposition of the current crisis depiction with a narrative case study centered on habitation and accommodation. From the theoretical analysis of the crisis and its associated emergency housing needs to the narrative depiction of spatial transformations within an apartment in Athens, the lingering question pertains to the feasibility of generalizing from abstract versions to tangible realities, from the familiar to the everyday.